CAP—advancing the evaluation of preclinical Alzheimer disease treatments (2016)
ABSTRACT: If we are to find treatments to postpone, reduce the risk of, or completely prevent the clinical onset of Alzheimer disease (AD), we need faster methods to evaluate promising preclinical AD treatments, new ways to work together in support of common goals, and a determination to expedite the initiation and performance of preclinical AD trials. In this article, we note some of the current challenges, opportunities and emerging strategies in preclinical AD treatment. We describe the Collaboration for Alzheimer's Prevention (CAP)-a convening, harmonizing and consensus-building initiative to help stakeholders advance AD prevention research with rigour, care and maximal impact-and we demonstrate the impact of CAP on the goals and design of new preclinical AD trials.